Characteristic appearance of spindle cell hemangiomatosis, often misdiagnosed as venous malformation: A retrospective study of 11 cases. Issue 12 (29th September 2020) - Liu, Hongyuan; Rao, Yamin; Gu, Hao; Yang, Xi; Hu, Li; Sun, Yi; Chen, Hui; Lin, Xiaoxi
Abstract: Spindle cell hemangiomatosis is a benign multifocal vascular proliferation that mostly occurs in the distal extremities. It is a relatively rare disease and causes difficulties in clinical diagnosis and differential diagnosis of venous malformation. We retrospectively assessed the medical history, and clinical features, imaging features, pathological features and follow up of 11 patients diagnosed pathologically with spindle cell hemangiomatosis after surgery. There are two types of clinical appearances in spindle cell hemangiomatosis in the distal extremities: bleb‐like nodules and varix‐like nodules. Bleb‐like nodules are mostly superficially located in the palm or interphalangeal joints with obvious hemorrhage in lesions and mainly composed of cavernous spaces rather than spindle cells. Varix‐like nodules are located in the back of the hands or arms with normal skin color and mainly composed of solid areas of accumulated spindle cells. Surgery is the standard therapy for spindle cell hemangiomatosis, while sclerotherapy is invalid. Despite the tendency to develop new lesions, there are no residual lesions at the surgical site during follow up. Bleb‐like nodules in the palm and interphalangeal joints are a typical clinical appearance in spindle cell hemangiomatosis which can help make clinical and a differential diagnosis of venous malformation. Surgery is the standard therapy for spindle cell hemangiomatosis with no residual lesions remaining at the surgical sites.